Amendment of mycorrhizae and its residual effect on growth and yield of maize (Zea mays) hybrids in coastal land (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rustikawati, Suprijono E, Murcitro BG, Herison C, Sitohang SJ. 2022. Amendment of mycorrhizae and its residual effect on growth and yield of maize (Zea mays) hybrids in coastal land. Biodiversitas 23: 5600-5605. Maize (Zea mays L.) is known sensitive to less optimal environmental conditions. Maize cultivation in coastal land has low productivity due to the availability of low nutrients and the ability to hold groundwater. The addition of mycorrhizal fungi (MF) to the coastal land is expected to improve the root environment suitable for plants. This study aimed to evaluate growth and yield of maize hybrids grown in coastal areas amended with MF and examining its residual effect. The newly developed hybrids, CT34 and CT17, and a commercial check cultivar, BISI-18, were grown on a coastal land with the application of mycorrhizae at the rate of 0, 5, and 10 g.plant-1 in a factorial experiment with three replications. Observations were made on plant height, stem diameter, number of leaves, leaf length, leaf width, leaf greenness, root fresh weight, ear length, ear diameter, number of grain rows, number of grain.ear-1, and grain weight.plant-1. Data were analyzed for ANOVA, and the mean comparisons were conducted with DMRT at a=5%. The results showed that there was no interaction effect between the maize hybrids and the rate of mycorrhizae on any observed variables. The new hybrid of CT34 showed almost similar growth to that of the check cultivar, BISI 18, but the yield was significantly lower. CT34 showed better performance than CT17 on all variables. The application of MF significantly increased stem diameter and root fresh weight, which in turn increased maize yields in the coastal land. Increasing the mycorrhizal rate up to 10 g.plant-1 in coastal lands was ineffective in increasing maize productivity compared to 5 g.plant-1. In a bioassay study on the mycorrhizal residues in the second season, the treatment of 10 g.plant-1 significantly increased maize growth by more than 100% compared to without mycorrhizae.
Keywords: Coastal land, hybrid maize, salinity